Pelatihan Dakwah Digital Bagi Remaja Masjid Hudallah Kondok untuk Optimalisasi Media Sosial - M. Ali Karmani (Indonesia, 2024)
The digital da'wah training for the youth of Hudallah Mosque in Kondok was motivated by the low utilization of social media as an effective medium for da'wah, leading to the aim of improving participants’ digital literacy and content production skills. The method used was participatory training involving 30 youths as participants, consisting of material presentations, content creation practice, publication simulations, and evaluations; data were collected through observation, questionnaires, and documentation, then analyzed descriptively. The results showed a significant increase in digital knowledge, da'wah content creation skills, and consistency in managing the mosque’s social media accounts after attending the training. In conclusion, the training proved effective in strengthening participants’ competencies and encouraging the formation of a sustainable digital da'wah team, thereby meeting the needs of da'wah in the technological era.